KUAUTAS MIKROBIOLOGI UDARA RUANG OPERASI RSUD dr. M. SOEWANDHIE SURABAYATAHUN 2014 - Nada Awang Abdillah; Erna Tri Astuti; Sudjarwo . (GEMA LINGKUNGAN KESEHATAN, 2014)
One of the rooms with very high risk of disease transmission in a hospital is the operatingroom.The government through the Minister of Health Decree No. 1204/MENKES/SK/X/2004on HospitalEnvironmental Health Requirements, has placed operating rooms as a very high risk zone. Among otherthings, air quality (bacterial count) is very important to note since the rooms are used for surgicalprocedures requiring extremely sterile conditions. This study was aimed at determining the air quality(bacterial count) in operating rooms at Dr. M. Soewandhie Hospital of Surabaya in 2014.This was a descriptive study, conducted in Dr. M. Soewandhie hospital. Samples were taken fromall operating rooms, RO 1 (one), RO 2 (two), RO 3 (three), RO4 (four) and RO 5 (five). Variables to beexamined induded air microbiological quality as reflected in the bacterial count, temperature and humiditymeasurements, assessment of building and construction cleaning and sterilization processes on operatingrooms.The results showed, that bacterial counts in RO 1 was 14 cfu/m3, RO 2 63 cfu/m3, RO 3 23cfu/m3, RO4 19 cfu/m3, these four rooms did not meet the requirement, the only room that satisfied therequirement was RO 5 as much as 5 cfu/m3. Temperature and humidity in RO 1 to RO 3 were at thesame value of 200e and 68%, RO4 was 21.50e and 59%, RO 5 was 210e and 60%. In terms of roomtemperature, all rooms were satisfactory, but in term of humidity, only RO4 was satisfactory. Results ofbuilding and room assessment were: RO 1 80%, RO 2 80%, RO3 84%, RO4 74% and RO 5 70%. Itcan be conduded that RO4 and RO 5 did not satisfy the standard. In terms of cleaning processes, RO 1to RO 3 were found equal at the percentage of 75%, while RO 4 and RO 5 was also equal at thepercentage of 65%.Among the five operating rooms at Soewandhie hospital of Surabaya, four of them have exceededthe bacterial count designated as the air quality standard . It is therefore recommended to performsterilization with UV(ultraviolet) before and after each surgery; to provide an exhaust fan in RO4 and RO5, to ensure conical meeting between the floors and walls of the ROs, installation of ceramic tiles on thewall of RO 5, keeping the operating room doors closed at all times, maintenance of air conditioning unitsand exhaust fans at least every 6 months to check up on the condition of the utilities and to develop andimplement standard operational procedures for cleaning and sterilization of process of cleaning theoperating rooms.